Endogenous glucose production, gluconeogenesis and liver glycogen concentration in obese non-diabetic patients - Müller, C.; Assimacopoulos-Jeannet, F.; Mosimann, F.; Schneiter, P.; Riou, J. P.; Pachiaudi, C.; Felber, J. P.; Jéquier, E.; Jeanrenaud, B.; Tappy, L. (Diabetologia, 1997)
Resting, post-absorptive endogenous glucose production (EGP), fractional gluconeogenesis and liver glycogen concentration were assessed in 6 lean and 5 obese non-diabetic subjects undergoing elective abdominal surgery. During the 2 days preceding these measurements, 0.3 g/day U-13C glucose had been added to their usual diet to label their endogenous glycogen stores. On the morning of day 3, EGP was measured with 6,6-2H glucose. Their endogenous 13C glycogen enrichment was calculated from 13CO2 and respiratory gas exchanges. Fractional gluconeogenesis was assessed as 1-(13C glucose/13C glycogen)100. EGP was similar in lean subjects (113 +/- 5 mg/min) and in obese subjects (111 +/- 6). Fractional gluconeogenesis was higher in obese (59 +/- 10%) than in lean subjects (29 +/- 8%). However, overall EGP remained constant due to a decrease in glycogenolysis. Since an increased gluconeogenesis and a decreased glycogenolysis may both contribute to increase liver glycogen concentration in obesity, hepatic glycogen concentrations were assessed in hepatic needle biopsies obtained during surgery. Hepatic glycogen concentrations were increased in obese patients (515 +/- 38 mg/g protein) compared to lean subjects (308 +/- 58, p < 0.05). It is concluded that in obese patients: a) fractional gluconeogenesis is increased; b) overall EGP is unchanged due to a proportional inhibition of glycogenolysis; c) liver glycogen concentration is increased.